Faktor-Faktor Yang Mempengaruhi Senjangan Anggaran Pada Instansi Pemerintah Sekretariat Jenderal Badan Pengawas Pemilihan Umum Republik Indonesia - Ardita, Elsa; Azwardi, Azwardi; Saftiana, Yulia (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2023)
This study aims to find empirical evidence to support that there are factors that influence budget length with the free variables of participatory budgeting, clarity of budget goals and organizational commitment. The research method uses multiple regression analysis. Data collection by distributing questionnaires directly at the General Secretariat of the Election Supervisory Agency. The results showed that participatory budgeting variables affect budget length, meaning that the higher the subordinates who participate in the budget preparation process, the higher the subordinates have the opportunity to do budget lengths. The variable clarity of budget goals has no effect on budget length, meaning that the higher the clarity of budget goals, it can reduce or minimize the occurrence of budget strains. The variable of organizational commitment affects the budget gap in the secretariat of the election supervisory body. The results of testing this hypothesis provide an understanding that changes in organizational commitments will have an effect on changes in the effectiveness of budget management.